2002
DOI: 10.1046/j.1369-6513.2002.00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing expertise: involving peer interviewers in qualitative research with hard‐to‐reach populations

Abstract: The use of peer interviewers with privileged access to a particular population group, which is difficult to reach via more conventional methods, has been acknowledged in recent research. This paper explores a number of key issues relating to the employment of peer interviewers by reflecting on a project designed to explore the views and experiences of parents who use illegal drugs. The project presented the research team with a number of challenges. These included the need to provide on‐going support for the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
153
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(156 citation statements)
references
References 11 publications
1
153
0
2
Order By: Relevance
“…The peer interviews (n=131) were carried out in the two largest cities, in the form of 'privileged-access interviewing', [39][40][41] by nine specially trained patients. The interviewers, five women and four men, were all stable in their recovery and had extensive contact networks comprising various groups of patients.…”
Section: Participants and Recruitmentmentioning
confidence: 99%
“…The peer interviews (n=131) were carried out in the two largest cities, in the form of 'privileged-access interviewing', [39][40][41] by nine specially trained patients. The interviewers, five women and four men, were all stable in their recovery and had extensive contact networks comprising various groups of patients.…”
Section: Participants and Recruitmentmentioning
confidence: 99%
“…Alternative approaches commonly used to recruit other “hard-to-reach” populations include time-location (or time-space) sampling, and venue-based sampling, where recruitment is conducted at times and locations within the community where groups of “hard-to-reach” populations are likely to be found (Karon, 2005) (e.g., Mutagoma et al, 2017; Wittenberg et al, 2015), indigenous field worker sampling, where individuals from the local community are trained to recruit and collect data in place of researchers (Shaghaghi et al, 2011) (e.g., Greene et al, 2009) and community-based outreach (e.g., Halcón & Lifson, 2004). Examples of successful recruitment into interview studies using such approaches are provided by Hunt, Moloney, and Fazio (2011) who used venue-based sampling, amongst other approaches, to recruit participants into an in-depth interview study about their drug use and youth culture, and by Elliott, Watson, and Harries (2002), who used peer interviewers to recruit and interview parents who use illegal drugs.…”
Section: Introductionmentioning
confidence: 99%
“…All four reports were observational evaluations of the impact of using peer interviewers. [21][22][23][24] With this type of involvement, the expected outcome is better quality data as a result of service users conducting interviews with their peers. This is reported to arise because the interviewees feel more at ease when interviewed by another service user and are therefore more comfortable in being open and honest about their experiences.…”
Section: The Evidence From Observational Evaluationmentioning
confidence: 99%
“…Three of these reported on the researchers' reflections on the outcomes. [22][23][24] The fourth study asked service user interviewees about their experiences of being interviewed by their peers. 21 One of the factors that these studies identified as influencing the outcome of this type of involvement was whether the service user interviewers had the requisite skills for the role.…”
Section: The Evidence From Observational Evaluationmentioning
confidence: 99%